Relative abundance and localization of interferon-stimulated gene 15 mRNA transcript in intra- and extra-uterine tissues during the early stages of pregnancy in sheep - Alak, Ilyas; Hitit, Mustafa; Kose, Mehmet; Kaya, M. Salih; Ucar, Eyyup Hakan; Atli, Zehra; Atli, Mehmet O. (Elsevier BV, 2020)
The aim of this study was to investigate relative abundance and localization of ISG15 mRNA transcript in intra-uterine (trophoblast, endometrium) and extra-uterine (hypothalamus, anterior pituitary, corpus luteum) tissues before and during the period of conceptus implantation. Multiparous ewes (n = 16) were randomly allotted into four groups: pregnant or estrous cyclic on days of 12 and 16 (n = 4 per group) following estrus. Relative abundances of ISG15 mRNA transcript were determined in the endometrium, corpus luteum, hypothalamus, and anterior-pituitary using real time quantitative PCR. Localization of ISG15 mRNA transcript was evaluated using in situ hybridization. The presence of ISG15 mRNA transcript was only visualized in intra-uterine tissues including the endometrium and trophoblast on day 12 of pregnancy. The ISG15 mRNA transcript was detected in all tissues evaluated on day 16 of pregnancy. The abundance of ISG15 mRNA transcript was greater in the endometrium on day 12 of pregnancy than at other days when evaluations occurred while in all other tissues except the hypothalamus there were large abundances of ISG15 mRNA on day 16 of pregnancy. It is concluded that the ISG15 mRNA transcript is only present in intra-uterine tissues before conceptus implantation. The ISG15 mRNA transcript, however, is present in extra-uterine tissues of ewes during implantation probably due to an increased amount of interferon-tau in blood circulation that is produced by the developing embryo. Results also indicate, for the first time, that pregnancy is associated with an intra-hypothalamus and anterior pituitary increased abundance of ISG15 mRNA transcript in ewes.
Keywords: Sheep; Hypothalamus; Isg15 Mrna; Gene Expression Regulation; Pregnancy; Animals; Cytokines; Female; Tissue Distribution; Ewes; RNA, Messenger; Anterior-Pituitary; Ubiquitins